ANALISIS PENERAPAN PAJAK PENGHASILAN FINAL PASAL 4 AYAT 2 ATAS JASA KONSTRUKSI PADA PT. REALITA TIMUR PERKASA - Ratuela, Hillary S.P; Sondakh, Jullie J.; Wangkar, Anneke (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
One source of domestic development financing is through the receipt of the tax sector which is one of the largest sources of revenue or income of the state. One type of tax is the Final Income Tax. Of the many taxpayers, construction services is one of the taxpayer, and one of the objects of the Final Income Tax. The purpose of this study is to analyze the implementation of the final income tax article 4 paragraph 2 on construction services at PT. Realita Timur Perkasa in this case concerning the calculation, cutting, deposit, and reporting of Final Income Tax Article 4 paragraph 2. The analytical method used is decriptive method. Based on the results of research obtained shows that the income tax rate Article 4 paragraph 2 that is charged by PT Realita Timur Perkasa that is 3%. For the implementation of tax obligations concerning tax reporting not yet in accordance with applicable taxation provisions. Should pay more attention to the provisions of taxation in this case the calculation, cutting, depositing, and reporting Income Tax Article 4 paragraph 2 of the construction services in order to be executed in accordance with applicable tax provisions.Â Keywords: Final Income Tax, Construction Services.